Pulmonary Telerehabilitation for People With Chronic Obstructive Pulmonary Disease in Brazil: A Mixed-Methods Feasibility Study - Luis H. G. Neves; Carla Malaguti; Marissa R. Santos; Laura A. Cabral; Laura B. D. da Silva; Hugo H. de Oliveira; Alessa S. S. Brugiolo; Anderson José; Anne E. Holland; Cristino C. Oliveira (International Journal of Telerehabilitation)
This study assessed the feasibility of pulmonary telerehabilitation’s (PTR) acceptability, implementation, practicality, and adaptation for people with Chronic Obstructive Pulmonary Disease (COPD) in Brazil. It also explored associations with clinical and socioeconomic features of Brazilians with COPD. This mixed-method study included thirty-one participants with COPD (age 62±10 years; FEV1= 72±14% predicted). Most participants (74.2%) reported good PTR session acceptability on the System Usability Scale and scores of ​4.6±0.3 and 4.5±0.6 on a 1-5 Likert-type scale of implementation and practicality, respectively. Participants suggested adaptations for better comfort on the exercise bike and varying exercise modalities. PTR acceptability was associated with participants’ younger age (rS=-0.57, p<0.01) and higher education (rS=0.51, p<0.01). PTR is feasible for people with COPD in Brazil regarding acceptability, implementation, practicality, and adaptation. Younger age and higher educational level are associated with greater PTR acceptability.